Characteristics of Climbing Plants Community in Rambut Island Wildlife Reserve - Rahayu, Nani; Hikmat, Agus; Tjitrosoedirjo, Soekisman (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Climbing plants are major component of tropical forest and play important role in many aspects of forest dynamic, balancing the micro-climate and provide food, shelter, nest material for wildlife especially bird. Inspite of their importance, climbing plants are often neglected. This research was aimed to describe the characteristics of climbing plants communities in three different ecosystems in Rambut Island Wildlife Reserve (RIWR). Climbing plants inventory in dryland, beach and ecotone forest were done by combining transect and quadrat method. The plots made in each ecosystem were 53, 27 and 85 respectively. A total of 37 climbing plants species consisted of 19 families were identifed and their contribution to species richness in RIWR reached 25,7 %. The climbing plants found in dryland, coastal and ecotone forest were 27 species (17 families), 23 species (16 families) dan 16 species (12 families) respectively. The species richness of climbing plants in all ecosystem were low, but the dryland forest was the richest due to the more fertile soils and vegetation structure complexity. In general, the species diversity and evenness in all ecosystem were low because of certain species domination. Dioscorea bulbifera was dominant in dryland and beach forest while Ipomoea violacea was dominant in ecotone forest. The domination of D. bulbifera influenced the similarity of climbing plants communities among ecosystem. Dominance, density and distribution of climbing plants indicated invasion of certain climbing plants species in RIWR. Keywords: diversity, forest, liana, vine